2013
DOI: 10.1074/jbc.m112.435461
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in Pluripotent Human Cells

Abstract: Background:Interferon signaling is an important component of innate immunity. Results: Human pluripotent cells fail to respond to interferon at least partly due to the high expression of an inhibitor of STAT1 phosphorylation, SOCS1. Conclusion: Pluripotent cells may be poised for the activation of interferon response upon differentiation. Significance: Pluripotency is associated with shutoff of a specific signal transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 52 publications
4
37
0
Order By: Relevance
“…Most of the IFN-induced ISGs are antiviral genes [27]. However, several ISGs have been found to be able to promote virus replication by negatively regulating the IFN pathway [28,29]. Here we identified 477 up-regulated genes and 551 down-regulated genes in ZIKV infected cells, which include many ISGs such as OAS2, IFIT3 and IFITM1 (Figure 1).…”
Section: Discussionmentioning
confidence: 80%
“…Most of the IFN-induced ISGs are antiviral genes [27]. However, several ISGs have been found to be able to promote virus replication by negatively regulating the IFN pathway [28,29]. Here we identified 477 up-regulated genes and 551 down-regulated genes in ZIKV infected cells, which include many ISGs such as OAS2, IFIT3 and IFITM1 (Figure 1).…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that iPS cells are defective in their antiviral response as a result of downregulation of key genes involved in immune response 25 , 26 . Similarly, attenuated antiviral response reported in human embryonic stem (ES) cells is restored by differentiation, suggesting that the impaired antiviral response of iPS cells likely stemmed from the pluripotent state and might promote cell pluripotency 25 , 26 , 34 .…”
Section: Discussionmentioning
confidence: 97%
“…The undifferentiated hESC and iPSC showed an attenuated type I interferon response that correspond to high expression of SOCS1, a suppressor of cytokine signaling factor (Hong and Carmichael 2013). Here, we demonstrate that the endodermal phase cells are responsive to type I IFN.…”
Section: Discussionmentioning
confidence: 99%
“…These cell types could also be exposed to infectious agents, such as pathogenic viruses and bacteria. In vitro experiments have shown that embryonic pluripotent stem cells can respond to type I (IFN-α and IFN-β) and II (IFN-γ) interferons that mediate the first line of defense against invading pathogens and generating specific immunity (Whyatt, Duwel et al 1993; Drukker, Katz et al 2002; Hong and Carmichael 2013). These observations are critical for understanding the innate immune function of pluripotent stem as well as progenitor cells and tissue rejection during cell therapy application.…”
Section: Introductionmentioning
confidence: 99%